Strategies for Activating Independent Learning Activities of Students in Biology Classes - Mykytyn, Tetiana; Dmytrus, Nataliia; Kapets, Nadiia; Gniezdilova, Victoria (Journal of Vasyl Stefanyk Precarpathian National University, 2024)
The article is dedicated to methods of activating students' independent learning activities during biology classes. It is proved that independent work in education holds significant importance for both the learning process and students of general secondary education. As noted by the authors of the article, the successful implementation of such activities depends on the teacher's ability to effectively manage them. Among the innovative methods there are: problem-based learning, projects and research, group work, utilization of internet resources and multimedia, task solving, and independent preparation of presentations or reports. By following these principles, it is possible to contribute to the development of students with their own worldview and a steadfast life position. The article highlights the importance of active independent learning activities during lessons, particularly in biology, and provides lesson plans developed using methods aimed at fostering such activities among seventh-grade students. Additionally, the results of student surveys are presented, demonstrating the level of interest in biological education, ranking of subjects in personal significance, level of students’ independent activity, and their suggestions for diversifying and improving the process of biology learning. It was revealed that 13% of students exhibit a high level of independent learning activity, 54% demonstrate an average level, while 32% have a low level of independent learning activity. It is noted that activation of students' independent learning activities in the process of studying biology is crucial for both their personal growth and overall development. As biology has its peculiarities, students' independent activity becomes the foundation for their success and the development of scientific thinking. Taking into account these aspects, it can be argued that students' independent cognitive activity in the study of biology is essential for their comprehensive development and the formation of scientific thinking and skills useful in future life and professional activities. According to the research, to achieve such results, teachers should create conditions conducive to the development of students' independence and cognitive abilities, providing them with the opportunity to independently explore, study, and conceptualize new knowledge.